2022
DOI: 10.3390/ceramics5030031
|View full text |Cite
|
Sign up to set email alerts
|

Possibilities of Mechanochemical Synthesis of Apatites with Different Ca/P Ratios

Abstract: Apatite is widely used in medicine as a biomaterial for bone tissue restoration. Properties of apatite depend on its composition, including the Ca/P ratio. This paper shows what range of Ca/P ratio can be attained in apatite by the mechanochemical method of synthesis, providing fast formation of a single-phase product. The synthesis was carried out from a reaction mixture of CaHPO4 and CaO at different Ca/P ratios in the range of 1.17–2.10. The products were studied by PXRD, FTIR and NMR spectroscopy, HRTEM, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…ePCL+ MgO 10 wt% presented a Ca/P ratio of 1.17, which can be reconducted to the formation of two possible products, namely dicalcium phosphate or Brushite with the chemical formula CaHPO 4 and the β-form of tricalcium phosphate Ca 3 (PO 4 ) 2 [ 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ePCL+ MgO 10 wt% presented a Ca/P ratio of 1.17, which can be reconducted to the formation of two possible products, namely dicalcium phosphate or Brushite with the chemical formula CaHPO 4 and the β-form of tricalcium phosphate Ca 3 (PO 4 ) 2 [ 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, all the samples showed new signals due to the degradation process: one broad peak at 3400 cm −1 related to the -OH stretching vibrations, and another signal around 1630 cm −1 that can be attributed to the carboxyl groups formed after the degradation [ 32 ]. Furthermore, after 28 days, the signals related to the growth of calcium apatite can be seen: in particular, two new sharp peaks at 596 cm −1 and 660 cm −1 that can be attributed to the bending vibrations of PO 4 3− and another signal at 909 cm −1 of the HPO 4 2− group [ 48 ]. Another relevant signal appeared at 1628 cm −1 that is attributed to hydroxyl liberation mode, and another peak at 1550 cm −1 is indicative of the vibrations of CO 3 2− [ 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that at x = 2, there is more water than is involved in the hydroxide formation. Water molecules present in the reaction mixture can be both sorbed by the surface of the particles and incorporated into the HA crystal lattice [ 21 , 22 ]. According to Table 1 , at x = 2, apatite with composition Ca 8.0 Zn 2.0 (PO 4 ) 4.0 (SiO 4 ) 2.0 should crystallize.…”
Section: Resultsmentioning
confidence: 99%
“…Although the XRD data indicated the presence of a large amount of an amorphous phase in the 2.0-ZnSi-HA sample, HRTEM showed that all particles were crystalline. This discrepancy can be explained by the fact that amorphous calcium phosphates are prone to crystallization under an electron beam due to intensive heating during HRTEM measurements [ 22 ]. Figure 6 shows that the distribution of the elements in the particles of 2.0-ZnSi-HA was uniform.…”
Section: Resultsmentioning
confidence: 99%
“…32 However, it is important to note that the exact ratio may not always be achieved due to variations in the precipitation environment, such as differences in pH value, 33 reaction temperature, and the presence of specific functional groups. 34 These factors can influence the extent of apatite formation and result in deviations from the precise stoichiometric ratio. The GelMA/HAMA scaffold contained many carboxylic acid groups that may be reacted with anthocyanidin-crosslinked samples to reduce active sites for mineral nucleation.…”
Section: In Vitro Bioactivity Studymentioning
confidence: 99%